Level IIb lymph node metastasis in transglottic laryngeal squamous cell carcinoma - Özkul, Yılmaz; Dündar, Rıza; İmre, Abdulkadir; Arslanoğlu, Seçil; Dinçer, Elif; Ateş, Düzgün; Pınar, Ercan; Önal, Kazım (ENT Updates, 2016)
Objective: To evaluate the clinical and pathologic parameters associated with level IIb metastasis in transglottic laryngeal carcinoma. Methods: A total of 238 laryngeal squamous cell carcinoma patients admitted to our tertiary center and surgically treated between January 2006 and January 2014. Of these 238 patients, 134 patients with transglottic laryngeal SCC were enrolled in the study. The type of neck dissection, the location of histopathologically proven metastatic lymph nodes, clinical N and T stages were reviewed. Palpable lymph nodes were accepted clinically cN(+) and the opposite as cN(-). Results: Of the 134 patients, 116 were diagnosed as cN(-), and 18 were as cN(+). Level IIb metastasis was diagnosed in 12 patients in the cN(+) group, and in two patients in the cN(-) group. Histopathological level IIb metastasis was shown in 14 of 134 patients, representing 16 of 268 neck dissection specimens. Level IIb metastasis was shown in the ipsilateral specimens in 12 patients and contralateral specimens in two patients. Forty-one of 134 patients presented cartilage invasion, and nine of them were diagnosed with level IIb metastasis. Conclusion: Thyroid cartilage invasion, the presence of level IIa invasion and advanced stage disease are the risk factors for level IIb metastasis. Therefore, level IIb should not be neglected during neck dissection in transglotticlaryngeal carcinoma.